1996
DOI: 10.1021/ja953524l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Reactivity, in the C−H Bond Activation of Cycloalkanes, of a Silica-Supported Tantalum(III) Monohydride Complex:  (⋮SiO)2TaIII−H

Abstract: Reaction of Ta[CH2C(CH3)3]3[CHC(CH3)3] (1) with a silica dehydroxylated at 500 °C has been previously reported to produce a mixture of ⋮SiOTa[CH2C(CH3)3]2[CHC(CH3)3] (2a) and (⋮SiO)2Ta[CH2C(CH3)3][CHC(CH3)3] (2b). Treatment of these two surface organometallic complexes under 1 atm of hydrogen up to 200 °C leads to the formation of a surface tantalum(III) monohydride:  (⋮SiO)2TaIIIH (3) as a major product and surface Si−H groups. 3 has been characterized in the following way:  it reversibly exchanges with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
140
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 34 publications
10
140
1
3
Order By: Relevance
“…[6] Similarly, the band at 2270 cm À1 is not affected by this treatment, and can be assigned to a n (SiÀH) . [3][4][5] Additionally, the band at 2961 cm À1 associated with the residual alkyl ligands (5 %, Figure 1 c) are modified, while a weak band at 2214 cm…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Similarly, the band at 2270 cm À1 is not affected by this treatment, and can be assigned to a n (SiÀH) . [3][4][5] Additionally, the band at 2961 cm À1 associated with the residual alkyl ligands (5 %, Figure 1 c) are modified, while a weak band at 2214 cm…”
mentioning
confidence: 99%
“…Moreover, in contrast to the tungsten hydride supported on alumina, [6] the IR spectrum of this supported tungsten hydride on silica-alumina, [W À H/SiO 2 -Al 2 O 3 ] SA (3) show several tungsten hydride bands, residual surface alkyl species as well as both Si À H and Al À H species. These latter hydride species are probably formed by the reaction of tungsten hydride intermediates with adjacent ( Si À O À Si ) and ( Si À O À Al s ) bridges, [3][4][5] thus providing bisgrafted species, [( SiO) 2 WH n ] and [( SiO)A C H T U N G T R E N N U N G (Al s O)WH n ] along with ( Si À H) and (Al s À H). The absence of SiH 2 species (not observed in the IR spectrum) [4] suggests the absence of formation of trisgrafted species.…”
mentioning
confidence: 99%
“…Any new reaction related to this challenge is important. In 1991, we discovered that the highly electrophilic earlytransition-metal hydride [(SiO) 3 Zr-H] supported on silica [1][2][3][4] could activate the C À H and C À C bonds of alkanes or polyolefins and could also catalyze the hydrogenolysis of these hydrocarbons into a range of gasolines.[5] Later, in 1997, we found that the highly electrophilic silica-supported tantalum hydride [(SiO) 2 TaH] [6,7] could transform any light alkane into its lower and higher homologues by both cleavage and formation of C À H and C À C bonds. We called this new catalytic reaction "alkane metathesis" by analogy to "olefin metathesis" [Eq.…”
mentioning
confidence: 99%
“…Also remarkable is the regenerative ability of the catalyst: after using TaH/KCC-1 in a 56 hour reaction it was regenerated by treatment with hydrogen (3 mL min À1 ) at 150 8C for 12 hours, after which it was used in another propene hydro-metathesis under identical reaction conditions and demonstrated slightly better activity (Figure 3 a, dotted lines), selectivity (see Figure S1 in the Supporting Information), and stability. The slight increase in the catalytic activity after regeneration could result from the fact that the total elimination of alkyl groups from TaNp/KCC-1 under H 2 requires heating up to 250 8C instead of 150 8C with Degussa silica [6] or MCM-41; [9] under these conditions the regeneration could help to remove more Np groups and produce a little bit more TaH than the first run.…”
mentioning
confidence: 99%
See 1 more Smart Citation